Transcranial ultrasound stimulation applied in ischemic stroke rehabilitation: A review - Guo, Jiecheng; Lo, Wai Leung Ambrose; Hu, Huijing; Yan, Li; Li, Le (Frontiers in Neuroscience, 2022)
Ischemic stroke is a serious medical condition that is caused by cerebral vascular occlusion and leads to neurological dysfunction. After stroke, patients suffer from long-term sensory, motor and cognitive impairment. Non-invasive neuromodulation technology has been widely studied in the field of stroke rehabilitation. Transcranial ultrasound stimulation (TUS), as a safe and non-invasive technique with deep penetration ability and a tiny focus, is an emerging technology. It can produce mechanical and thermal effects by delivering sound waves to brain tissue that can induce the production of neurotrophic factors (NFs) in the brain, and reduce cell apoptosis and the inflammatory response. TUS, which involves application of an acoustic wave, can also dissolve blood clots and be used to deliver therapeutic drugs to the ischemic region. TUS has great potential in the treatment of ischemic stroke. Future advancements in imaging and parameter optimization will improve the safety and efficacy of this technology in the treatment of ischemic stroke.